2022
DOI: 10.3390/nano12030548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Temperature on Density and Electrical Characteristics of Hf0.5Zr0.5O2 Thin Films Prepared by Plasma-Enhanced Atomic Layer Deposition

Abstract: HfxZr1−xO2 (HZO) thin films have excellent potential for application in various devices, including ferroelectric transistors and semiconductor memories. However, such applications are hindered by the low remanent polarization (Pr) and fatigue endurance of these films. To overcome these limitations, in this study, HZO thin films were fabricated via plasma-enhanced atomic layer deposition (PEALD), and the effects of the deposition and post-annealing temperatures on the density, crystallinity, and electrical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Under the optimized process conditions reported in our previous studies [27,28], MIS capacitors were fabricated by depositing DP-and RP-HfO 2 thin films on p-Si wafers and developing Pt electrodes. HfO 2 thin films were deposited by splitting the temperature in the range of 200-260 • C, which was considered the process window, and the thickness of the deposited film was determined to be approximately 10 nm by the ellipsometer.…”
Section: Resultsmentioning
confidence: 99%
“…Under the optimized process conditions reported in our previous studies [27,28], MIS capacitors were fabricated by depositing DP-and RP-HfO 2 thin films on p-Si wafers and developing Pt electrodes. HfO 2 thin films were deposited by splitting the temperature in the range of 200-260 • C, which was considered the process window, and the thickness of the deposited film was determined to be approximately 10 nm by the ellipsometer.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al fabricated Hf 0.5 Zr 0.5 O 2 thin films via plasma-enhanced atomic layer deposition. A high remanent polarization with 2 P r of 38.2 μC/cm 2 and an excellent fatigue endurance of 2.5 × 10 7 cycles were obtained by regulating the deposition temperature, post-annealing temperature and RF plasma discharge time [ 1 ]. Among the studies about Hf x Zr 1-x O 2 , the work in this study showed relatively good remanent polarization and fatigue endurance performances despite being under the lowest deposition temperature.…”
mentioning
confidence: 99%